Association of Serum Bilirubin and Functional Variants of Heme Oxygenase 1 and Bilirubin UDP-Glucuronosyl Transferase Genes in Czech Adult Patients with Non-Alcoholic Fatty Liver Disease - Jaromír Petrtýl; Karel Dvořák; Jan Stříteský; Martin Leníček; Alena Jirásková; Václav Šmíd; Martin Haluzík; Radan Brůha; Libor Vítek (MDPI AG, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disorder worldwide. The aim of our study was to assess the role of bilirubin, and the heme oxygenase 1 (HMOX1) and bilirubin UDP-glucuronosyl transferase (UGT1A1) promoter gene variants, which are involved in bilirubin homeostasis, in the NAFLD development in adult patients. The study was performed on 84 patients with NAFLD and 103 age/sex-matched controls. Routine biochemistry, inflammatory markers, adipokines, and the fibrosis/steatohepatitis stage were determined in the NAFLD patients. The (GT)n/(TA)n dinucleotide variations in HMOX1/UGT1A1 gene promoters, respectively, were analyzed by fragment analysis. Compared to controls, serum bilirubin concentrations in NAFLD patients tended to be decreased, while the prevalence of phenotypic Gilbert syndrome was significantly low. Genetic variations in HMOX1 and UGT1A1 gene promoters did not differ between NAFLD patients and controls, and no relationship was found in the NAFLD patients between these gene variants and any of the laboratory or histological parameters. In conclusion, metabolism of bilirubin is dysregulated in NAFLD patients, most likely due to increased oxidative stress, since frequencies of the major functional variants in the HMOX1 or UGT1A1 gene promoters did not have any effect on development of NAFLD in adult patients.